Super-resolution fluorescence microscopy by line-scanning with an unmodified two-photon microscope - Pilger, Christian; Pospíšil, Jakub; Müller, Marcel; Ruoff, Martin; Schütte, Martin; Spiecker, Heinrich; Huser, Thomas (Philosophical transactions. Series A, Mathematical, physical, and engineering sciences, 2021)
Fluorescence-based microscopy as one of the standard tools in biomedical research benefits more and more from super-resolution methods, which offer enhanced spatial resolution allowing insights into new biological processes. A typical drawback of using these methods is the need for new, complex optical set-ups. This becomes even more significant when using two-photon fluorescence excitation, which offers deep tissue imaging and excellent z-sectioning. We show that the generation of striped-illumination patterns in two-photon laser scanning microscopy can readily be exploited for achieving optical super-resolution and contrast enhancement using open-source image reconstruction software. The special appeal of this approach is that even in the case of a commercial two-photon laser scanning microscope no optomechanical modifications are required to achieve this modality. Modifying the scanning software with a custom-written macro to address the scanning mirrors in combination with rapid intensity switching by an electro-optic modulator is sufficient to accomplish the acquisition of two-photon striped-illumination patterns on an sCMOS camera. We demonstrate and analyse the resulting resolution improvement by applying different recently published image resolution evaluation procedures to the reconstructed filtered widefield and super-resolved images. This article is part of the Theo Murphy meeting issue 'Super-resolution structured illumination microscopy (part 1)'.
Keywords: Animals; Kidney; mikroskopie fluorescenční multifotonová; optické prostředky; software; SIM; Optical Phenomena; Optical Devices; Mice; Convallaria; optické jevy; Algorithms; myši; laser scanning fluorescence microscopy; super-resolution optical microscopy; počítačové zpracování obrazu; structured illumination microscopy; Microscopy, Fluorescence, Multiphoton; algoritmy; Software; multi-photon fluorescence excitation; zvířata; ledviny; Image Processing, Computer-Assisted